Zinc Oxide Nanoparticles for Enhancing Students’ View of the Nature of Science and Technology - Priyand, Elza Rachman Panca; Sukmafitri, Ajeng; Mudzakir, Ahmad; Nandiyanto, Asep Bayu Dani; Nugraha, Willy Cahya; Ramdhani, Wahyu (Universitas Pendidikan Indonesia, 2020)
This study aims to evaluate zinc oxide (ZnO) nanoparticles as a learning media to enhance students' understanding of View of Nature of Science and Technology (VNOST). The method used in this study: (i) understanding how to synthesize ZnO nanoparticles using a liquid-phase synthesis; (ii) implementation of ZnO nanoparticles to students and analysis their comprehension using Transcript Based Lesson Analysis (TBLA) on the Learning Video Recording and Adaptation Learning Transcript VNOST questionnaire, which is linked to the implementation and pattern of knowledge construction; and (iii) descriptive qualitative analysis to analyze the understanding of VNOST for each Category (Naïve, Has Merit and Realist). To support this study, several analyses were done, such as a scanning electron microscope and X-ray diffraction to characterize ZnO nanoparticles’ morphology and crystal structure, respectively, prior to giving this material for further learning to students. Experimental results showed that the use of ZnO nanoparticles is effective to improve the student comprehension. The understanding in the principle of nucleation and growth can be explained well since the reaction of ZnO is relatively fast. Students became more serious in listening during the learning process and more curious to study science and technology. Based on a comparative analysis of the initial and final ability of VNOST, it is proved that there was a change in students' views related to science and technology.